Estimating the contribution of occupational solar ultraviolet exposure to skin cancer. (1st January 2014) - Milon, A.; Bulliard, J.‐L.; Vuilleumier, L.; Danuser, B.; Vernez, D.
Summary: Background: Exposure to solar ultraviolet (UV) radiation is the main causative factor for skin cancer. Outdoor workers are at particular risk because they spend long working hours outside, may have little shade available and are bound to take their lunch at their workplace. Despite epidemiological evidence of a doubling in risk of squamous cell carcinoma (SCC) in outdoor workers, the recognition of skin cancer as an occupational disease remains scarce. Objectives: To assess occupational solar UV doses and their contribution to skin cancer risk. Methods: A numerical model (SimUVEx) was used to assess occupational and lunch break UV exposure, and to characterize exposure patterns and anatomical distribution. Risk of SCC was estimated from an existing epidemiological model. Results: Horizontal body locations received 2·0–2·5 times more UV than vertical locations. The dose associated with having lunch outdoors every day was similar to that from doing outdoor work 1 day per week, but only half that of a seasonal worker. Outdoor work is associated with an increased risk of SCC and also with frequent acute episodes. Conclusions: Occupational solar exposure contributes greatly to overall lifetime UV dose, resulting in an excess risk of SCC. The magnitude of the estimated excess in risk supports the recognition of SCC as an occupational disease.